17β-estradiol promotes acute refeeding in hungry mice via membrane-initiated ERα signaling - Kaifan Yu; Yanlin He; Ilirjana Hyseni; Zhou Pei; Yongjie Yang; Pingwen Xu; Xing Cai; Hesong Liu; Na Qu; Hailan Liu; Yang He; Meng Yu; et al. (Elsevier, 2020)
Objective: Estrogen protects animals from obesity through estrogen receptor α (ERα), partially by inhibiting overeating in animals fed ad libitum. However, the effects of estrogen on feeding behavior in hungry animals remain unclear. In this study, we examined the roles of 17β-estradiol (E2) and ERα in the regulation of feeding in hungry female animals and explored the underlying mechanisms. Methods: Wild-type female mice with surgical depletion of endogenous estrogens were used to examine the effects of E2 supplementation on acute refeeding behavior after starvation. ERα-C451A mutant mice deficient in membrane-bound ERα activity and ERα-AF20 mutant mice lacking ERα transcriptional activity were used to further examine mechanisms underlying acute feeding triggered by either fasting or central glucopenia (induced by intracerebroventricular injections of 2-deoxy-D-glucose). We also used electrophysiology to explore the impact of these ERα mutations on the neural activities of ERα neurons in the hypothalamus. Results: In the wild-type female mice, ovariectomy reduced fasting-induced refeeding, which was restored by E2 supplementation. The ERα-C451A mutation, but not the ERα-AF20 mutation, attenuated acute feeding induced by either fasting or central glucopenia. The ERα-C451A mutation consistently impaired the neural responses of hypothalamic ERα neurons to hypoglycemia. Conclusion: In addition to previous evidence that estrogen reduces deviations in energy balance by inhibiting eating at a satiated state, our findings demonstrate the unexpected role of E2 that promotes eating in hungry mice, also contributing to the stability of energy homeostasis. This latter effect specifically requires membrane-bound ERα activity.